2023
DOI: 10.1136/rmdopen-2022-002935
|View full text |Cite
|
Sign up to set email alerts
|

Risk of relapse of ANCA-associated vasculitis among patients homozygous for the proteinase 3 gene Val119Ile polymorphism

Abstract: BackgroundThe frequency of proteinase 3 gene (PRTN3) polymorphisms in patients with antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is not fully characterised. We hypothesise that the presence of a PRTN3 gene polymorphism (single nucleotide polymorphism (SNP) rs351111) is relevant for clinical outcomes.MethodsDNA variant calling for SNP rs351111 (chr.19:844020, c.355G>A) in PRTN3 gene assessed the allelic frequency in patients with PR3-AAV included in the Rituximab in ANCA-Associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Several authors studied the association of certain SNPs in the human leukocyte antigen (HLA) regions and found differences in frequency according to ANCA specificity (myeloperoxidase (MPO) or proteinase-3 (PR3)) [ 14 , 15 ]. Casal Moura et al found an association of rs351111, located in the PR3 gene, with a higher frequency of severe relapses in a cohort of 188 patients [ 16 ]. Certain TLR9 , protein tyrosine phosphatase non-receptor type 22 ( PTPN22 ), and IL2 receptor-A SNPs involved in lymphocyte activation pathways have also been associated with higher disease susceptibility, suggesting their pathophysiologic role [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors studied the association of certain SNPs in the human leukocyte antigen (HLA) regions and found differences in frequency according to ANCA specificity (myeloperoxidase (MPO) or proteinase-3 (PR3)) [ 14 , 15 ]. Casal Moura et al found an association of rs351111, located in the PR3 gene, with a higher frequency of severe relapses in a cohort of 188 patients [ 16 ]. Certain TLR9 , protein tyrosine phosphatase non-receptor type 22 ( PTPN22 ), and IL2 receptor-A SNPs involved in lymphocyte activation pathways have also been associated with higher disease susceptibility, suggesting their pathophysiologic role [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%